The Effectiveness Of Using TPACK-Integrated Learning Media On The Learning Outcomes Of Exponentiation Among Eighth-Grade Students - Rizkiana, Nila; Sridana, Nyoman; Kurniawan, Eka (Sigma&Mu: Journal of Mathematics Education, Mathematics, Statistics and Data Science, 2025)
The background of this study is the low student learning outcomes, the ineffective learning process, and the lack of teacher interaction. This research aims to examine the effectiveness of using TPACK-integrated learning media on the learning outcomes of exponent numbers among eighth-grade students at SMP Negeri 1 Kediri. The research approach used is quantitative, with a research design of Pretest-Posttest Only Control Group Design. The population in this study includes all eighth-grade students at SMPN 1 Kediri, and the sampling technique used is purposive sampling. The selected sample consists of class VIIIC as the control group and class VIIIE as the experimental group. The research instruments include test questions, observations, and student response questionnaires. The data analysis techniques used in this study are descriptive and inferential statistical analysis. The learning media used include instructional videos, Liveworksheets-based LKPD, and Kahoot. The results of the study indicate that the use of TPACK-integrated learning media is effective in improving the learning outcomes of exponent numbers among eighth-grade students at SMP Negeri 1 Kediri in the 2024/2025 academic year. This effectiveness is demonstrated by: (1) An increase in the average learning outcomes of the experimental class by 0.7342, which falls into the high category. (2) A significant difference in the average mathematics learning outcomes between the control and experimental classes, as indicated by the independent sample t-test, where t_calculated > t_table (6.104 > 2.005).